TEACHERS’ AND STUDENTS’ PERCEPTIONS ABOUT CLASSROOM-BASED SPEAKING TESTS - Norbekova, Gulruh (Журнал иностранных языков и лингвистики, 2021)
As it is clear for everyone, teaching a foreign language is considerably important mission in such active days that communicating in foreign language is being required highly. That means we should deal with the latest innovative teaching methods not limiting with only inherited stable trends in our classroom. For this aim, testing is considered as an indispensable part of the teaching and learning processes. Since testing, teaching, and learning are closely related, it is inevitable for them to have an influence on each other. Tests are thought to affect teaching and learning positively or negatively.